BEHAVIORAL SYMPTOMS AMONG VETERANS WITH CO-OCCURRING POSTTRAUMATIC STRESS DISORDER AND DEMENTIA. (11th November 2018) - Kang, B; Karel, M J; Corazzini, K; Pan, W; McConnell, E S
Abstract: Veterans with dementia and posttraumatic stress disorder (PTSD) in residential care facilities are likely to encounter a range of trauma-related environmental stimuli that may trigger behavioral symptoms of dementia (BSD). Most studies of BSD do not examine the impact of trauma or PTSD on BSD. This study examines how BSD, interpersonal and environmental triggers, and care plans vary depending on the presence of PTSD or combat exposure among veterans with dementia. This mixed-method, secondary analysis study uses program evaluation data from the STAR-VA behavioral intervention program, implemented in 76 VA Community Living Centers between 2013 and 2016. Among 315 veterans enrolled in this program, 45% had a history of combat exposure, and 26% had PTSD. Results highlight a range of triggers amenable to intervention, such as overstimulation. The similarities and differences between veterans with and without PTSD are discussed in relation to enhancing person-centered dementia care for older veterans.